Penggunaan media puzzle pecahan biasa pada pembelajaran matematika untuk meningkatkan pemahaman siswa pada materi pecahan - Saryanti, Endah (Jurnal Pendidikan Dasar, 2022)
The use of media can help teachers to realize student-centered learning with fun and meaningful learning. Writing this best practice report aims to describe the use of ordinary fraction puzzle media in learning mathematics for third grade students at SD Negeri Kleco II. Learning using puzzle media proves that the use of ordinary fraction puzzle media can increase students' understanding of simple fraction material and is able to create a fun and meaningful learning atmosphere for students. The use of ordinary fraction puzzle media is able to provide two-way communication for teachers and students which makes it easier for teachers and students to interact with each other in learning. Ordinary fraction puzzle media involves active participation of students in learning so that students can explore their knowledge.